Confluence of Interests in the Translations of Ake: the Years of Childhood and Aké: ní Ìgbà Èwe: An Appraisal of Language Retrieval and Translation (2021)
There are different motivating factors for a literary artist to venture into translation business. With the introduction of Akinwumi Isola’s Language Retrieval, a new dimension to the study of African languages translations was presented, especially as regards the classification of translators and texts. This study explores the interests behind the literary translation of Wole Soyinka’s and Akinwumi Isola’s translations of Ake with a view to establishing the features of translation and language retrieval. Findings show that even though both authors employed the same strategies, e.g. language transposition and equivalence, they diverged with respect to certain features. While translation exhibits two different cultures and languages, language retrieval exhibits the same culture but different languages.